2021
DOI: 10.3390/pharmaceutics13020254
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Drug Design with a Noncharged Carrier for Mitochondrial Delivery

Abstract: Recently, it was proposed that the thiophene ring is capable of promoting mitochondrial accumulation when linked to fluorescent markers. As a noncharged group, thiophene presents several advantages from a synthetic point of view, making it easier to incorporate such a side moiety into different molecules. Herein, we confirm the general applicability of the thiophene group as a mitochondrial carrier for drugs and fluorescent markers based on a new concept of nonprotonable, noncharged transporter. We implemented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Moreover, the variations in pH also correlated with differential responses to some metabolic drugs [ 39 ]. In a second work, we observed different sensitivity responses of breast cancer models to a chimeric small molecule developed for delivering the pyruvate dehydrogenase kinase inhibitor dichloroacetate to mitochondria [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the variations in pH also correlated with differential responses to some metabolic drugs [ 39 ]. In a second work, we observed different sensitivity responses of breast cancer models to a chimeric small molecule developed for delivering the pyruvate dehydrogenase kinase inhibitor dichloroacetate to mitochondria [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Mitochondria-selective accumulation of compounds can be accomplished by some cationic moieties commonly known as delocalised lipophilic cations (DLCs), [5][6][7][8] and this ability is frequently attributed to their delocalised cationic charge, resulting in increased lipid membrane permeability and accumulation within the negatively-charged mitochondrial matrix in accordance with the Nernst equation. 7,9 While there are a broad range of mitochondrial targeting species, from rhodamines, cyanines, mitochondrial-targeting peptides to thiophene-based vectors, 8,[10][11][12][13] triphenylphosphonium-based vectors are arguably the most widely used and have been applied for the delivery of numerous molecular cargoes as highlighted in the literature. 14 Due to the success in applying triphenylphosphonium (TPP + ) systems for mitochondrial delivery, there is an increasing interest in modifying the TPP + systems for enhanced delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Ripoll et al, have showed promising new carrier to target mitochondria based on nonprotonable, noncharged thiophene ring. Authors used this construction to prepare chimeric drug deliver using the carrier and pyruvate dehydrogenase kinase inhibitor dichloroacetate demonstrating utility of thiophene moiety as a noncharged carrier for targeting mitochondria with metabolism-targeting drugs [11]. Alternatively, the drugs maybe designed specifically.…”
mentioning
confidence: 99%
“…In conclusion, this Special Issue underlines importance of mitochondria in pathophysiological situation such as: genetic disorders [1,2], cardiovascular diseases [3,4], inflammation [5] and cancer [6][7][8][9][10]. Indicates new tools to selective target mitochondria in order to: rescue aberrant cell phenotype, change cell metabolism or induces mitochondria dependent cell death [1][2][3][4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%